An empirical comparison of structural and accounting-based credit risk models. - Leong, Wai Fun. (2009)
This paper looks into 3 types of credit risk models: Altman Z-Score (2002), KMV-Merton (1974) and Longstaff and Schwartz (1997). These models are analyzed and tested using a sample of listed industrial firms in the Standard & Poor’s 500.